2011
DOI: 10.1097/wco.0b013e328348bda5
|View full text |Cite
|
Sign up to set email alerts
|

The prominent role of stimulus processing

Abstract: Purpose of review The present review develops a framework from which to understand the role of the cholinergic system in healthy cognition and in cognitive dysfunction. Traditionally, the cholinergic system has been thought to have direct influence on cognitive processes such as working memory and attention. Although the influence of cholinergic function on stimulus processing has been long appreciated, the notion that cholinergic effects on stimulus processing is the mechanism by which acetylcholine influence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 41 publications
(26 citation statements)
references
References 100 publications
1
25
0
Order By: Relevance
“…We specifically aimed to investigate whether the impairments of selective attention manifest in depressed subjects would improve under antimuscarinic challenge. Muscarinic cholinergic mechanisms facilitate the processing of sensory information and play a major role in selective attention processing, such that deviations from an optimal range of cholinergic function in either direction can impair attention (3236). Based upon the evidence that muscarinic receptors are hypersensitive in depressed patients, we hypothesized that selective attention would improve under antimuscarinic challenge.…”
Section: Pilot Dose-finding Study Suggests Rapid Antidepressant Respomentioning
confidence: 99%
“…We specifically aimed to investigate whether the impairments of selective attention manifest in depressed subjects would improve under antimuscarinic challenge. Muscarinic cholinergic mechanisms facilitate the processing of sensory information and play a major role in selective attention processing, such that deviations from an optimal range of cholinergic function in either direction can impair attention (3236). Based upon the evidence that muscarinic receptors are hypersensitive in depressed patients, we hypothesized that selective attention would improve under antimuscarinic challenge.…”
Section: Pilot Dose-finding Study Suggests Rapid Antidepressant Respomentioning
confidence: 99%
“…While the cholinergic system is important in multiple cognitive domains, including memory and attention, the literature suggests that the modulation of these functions may occur via stimulus processing mechanisms (Bentley et al, 2011; Furey, 2011). At a behavioral level, cholinergic modulation produced stimulus specific behavioral effects during attention tasks, consistent with the modulation of the relative salience of competing visual stimuli (Bentley et al, 2003a; Furey et al, 2008a).…”
Section: Introductionmentioning
confidence: 99%
“…Functional brain imaging studies have demonstrated that cholinergic enhancement selectively increases neural activity in medial visual processing areas while reducing neural responses in lateral visual extrastriate cortex (Bentley et al, 2003a, b; Furey et al, 2000c; Furey et al, 2008b; Ricciardi et al, 2009) and in task-relevant prefrontal and parietal cortical regions (Bentley et al, 2004; Bentley et al, 2003a, b; Freo et al, 2005; Furey et al, 2000c; Furey et al, 1997; Furey et al, 2008b; Ricciardi et al, 2009). As these response modulations were accompanied by improved task performance, we hypothesized that these changes in brain response are associated with an enhanced visual percept that rendered the task easier to perform (Furey, 2011; Furey et al, 2000c). More specifically, the increased processing in medial visual cortex may underlie a superior representation of the stimulus being processed, which renders the task easier to perform and reduces the need to recruit prefrontal cortex.…”
Section: Introductionmentioning
confidence: 99%
“…The hyperresponsive muscarinic cholinergic system, together with the role of acetylcholine in cognitive functioning, 13 led to the hypothesis that cholinergic dysfunction contributed to the cognitive features observed in depression. Thus, scopolamine was administered to evaluate the cognitive impact of blocking muscarinic receptors.…”
Section: Antidepressant Effectsmentioning
confidence: 99%